2018
DOI: 10.1016/j.jclepro.2018.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Local strategies for China's carbon mitigation: An investigation of Chinese city-level CO2 emissions

Abstract: This paper provides a systematic analysis that identifies the driving forces of carbon dioxide (CO2) emissions of 286 Chinese prefecture-level cities in 2012. The regression analysis confirms the economic scale and structure effects on cities' CO2 emissions in China. If China's annual economic growth continues at the rate of 7%, CO2 emissions will increase by about 6% annually. In addition, climate conditions, urbanization and public investment in R&D are identified as important driving forces to increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…From an LCE perspective, China's nascent manufacturing industry is the dominant driving force for energy consumption, and a significant source of pollution, carbon emissions (70%), and waste generation, which impose high costs on the economy, urban public health, and the environment [1,19]. In fact, Cai et al [30] found that economic scale and structure is the main among ten driving forces of GHG emissions in 286 prefecture cities, where a current economic trajectory of 7% GDP growth can lead to 6% growth of CO 2 emissions. Such findings support the dominance of economic strategies in LCC pilots [8,81].…”
Section: Integrationmentioning
confidence: 99%
See 3 more Smart Citations
“…From an LCE perspective, China's nascent manufacturing industry is the dominant driving force for energy consumption, and a significant source of pollution, carbon emissions (70%), and waste generation, which impose high costs on the economy, urban public health, and the environment [1,19]. In fact, Cai et al [30] found that economic scale and structure is the main among ten driving forces of GHG emissions in 286 prefecture cities, where a current economic trajectory of 7% GDP growth can lead to 6% growth of CO 2 emissions. Such findings support the dominance of economic strategies in LCC pilots [8,81].…”
Section: Integrationmentioning
confidence: 99%
“…This is done to build urban resilience in response to climatic stimuli [56]. Therefore, the urgent development and implementation of balanced adaptation strategies in these cities integrate climate risk management into climate-smart investment to increase the cities' adaptive capacities and improve agriculture, urban forestry, urban coastlines, water adaptation ability, and hazard mitigation [30,151]. With this being said, most of the strategies and discussions focus on mitigation [58]; and there is a lack of cohesion between mitigation and adaptation strategies, which can lead to maladaptation [30,50].…”
Section: Sub-dimensions Components Strategies Identified In the Litermentioning
confidence: 99%
See 2 more Smart Citations
“…Structuring calculated CO 2 emissions over time and space in an absolute manner had increasingly been regarded as the potential approach to discontinuing CO 2 emissions (Cai et al, 2018;Liu et al, 2010;Liu et al, 2012;Tan and Lu, 2015). On one hand, structural analysis techniques (basically including structural decomposition analysis, index decomposition analysis and production-theoretical decomposition analysis) (Li et al, 2017a;Wei et al, 2017) and econometric models (Guan et al, 2018;Meng et al, 2011) have been widely employed in exploring structural patterns in the form of aggregate relative importance, without discussing the role of absolute values in absolute emissions.…”
Section: Introductionmentioning
confidence: 99%